# 2 Answers

**........................and the reason you cannot solve for "x" is because you do not have a complete equation. The two fractions would need to equal something. If you complete the equation (i.e. ****(4x + 3)/13 = 3 ) THEN you could calculate for "x"**

(4x + 3)/13 = 39/13 (changed the whole number to a fraction)

(4x + 3) -3/13 = 39/13 - 3/13

4x/13 = 36/13

4x/13 (dvidied by 4/13) ** ** = 36/13 divided by 4/13

x = 36/13 X 13/4

x = 468/52

x = 9

(Now substitute 9 for x and see if you balance)

4(9) + 3/13 = 3

36 + 3/13 = 3

39/13 = 3

3 = 3

whooooopeeeee

13 years ago. Rating: 0 | |

### Top contributors in Science & Mathematics category

### Unanswered Questions

Cây xanh Tân Thúy

Answers: 0
Views: 8
Rating: 0

sv388pink1

Answers: 0
Views: 8
Rating: 0

xin88luxury

Answers: 0
Views: 9
Rating: 0

vb777nemphucnhangia

Answers: 0
Views: 12
Rating: 0

8xbet1880

Answers: 0
Views: 13
Rating: 0

kuwinmobi1

Answers: 0
Views: 16
Rating: 0

n88s4com

Answers: 0
Views: 10
Rating: 0

YEU88

> More questions...
Answers: 0
Views: 17
Rating: 0